Aspects of education for democratic citizenship in post-war Germany - Phillips, D (2012)
This paper examines aspects of education for democracy in occupied Germany, 1945-1949, with a focus on efforts made in the British Zone of Occupation to encourage active participation in democratic processes in schools and universities. © 2012 Copyright Taylor and Francis Group, LLC.